2008
DOI: 10.1021/es8012529
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Anodic Metabolic Function on Bioelectricity Generation and Substrate Degradation in Single Chambered Microbial Fuel Cell

Abstract: Influence of anodic metabolic function viz., aerobic, anoxic and anaerobic on bioelectricity generation was evaluated in single chamber mediatorless microbial fuel cells (non-catalyzed graphite electrodes; open-air cathode) during wastewater treatment under similar operating conditions (pH 7; ambient temperature/pressure). Despite the fluctuations observed, aerobic metabolic function (379 mV; 538 mA/m2) documented higher power generation compared to anoxic (251 mV; 348 mA/m2) and anaerobic (265 mV; 211 mA/m2) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
12
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 98 publications
(12 citation statements)
references
References 42 publications
0
12
0
Order By: Relevance
“…17). Current production in microaerobic environments exceeds that of strict anaerobic conditions and could be a result of production of electron shuttles under microaerobic conditions (Mohan, et al 2008). This could explain why the biofilm of the pyomelanin hyper producer was thicker at the medium surface but the pyomelanin deficient strain had consistent biofilm thickness along the working electrode.…”
Section: Microbial Production Of Electric Currentmentioning
confidence: 99%
“…17). Current production in microaerobic environments exceeds that of strict anaerobic conditions and could be a result of production of electron shuttles under microaerobic conditions (Mohan, et al 2008). This could explain why the biofilm of the pyomelanin hyper producer was thicker at the medium surface but the pyomelanin deficient strain had consistent biofilm thickness along the working electrode.…”
Section: Microbial Production Of Electric Currentmentioning
confidence: 99%
“…MFCs harvest energy from oxidation of organic compounds including those present in wastewaters. The majority of MFCs operate under anaerobic conditions, though a few aerobic MFCs have been developed recently (Biffinger et al, 2008;Mohan et al, 2008). Considering that sunlight offers an unlimited source of energy, development of self-sustainable microbial fuel cells that rely on light instead of organics as an energy source has become an increasingly popular area of research in recent years (Cao et al, 2008;He et al, 2009;Malik et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…The electrochemical activity was enhanced by the hybrid bacterial attachment over the electrode 36 . COD removal efficiency increased with increase in initial concentration 37 . It can also be observed that COD removal too was higher for FePc/MWCNT than other electrodes.…”
mentioning
confidence: 88%